Proteoglycan production by human glomerular visceral epithelial cells and mesangial cells in vitro. - van Det, N F (1995)
Proteoglycans metabolically labelled with [35S]sulphate and [3H]glucosamine or [3H]leucine were isolated from the incubation medium and cell layer of human adult mesangial cells and glomerular visceral epithelial cells using sequential DEAE chromatography purification steps followed by gel-filtration chromatography. The proteoglycan composition of each peak was analysed by treatment with HNO2, chondroitinase ABC or chondroitinase AC followed by chromatography on Sephadex G-50 columns. Heparan sulphate proteoglycan (HSPG) and dermatan sulphate proteoglycan were detected in both the culture medium and cell layer of mesangial cells. Culture medium of glomerular visceral epithelial cells contained HSPG and a second proteoglycan with the properties of a hybrid molecule containing HS and chondroitin sulphate (CS). The cell layer contained HSPG and CSPG. Detailed analysis of the hybrid molecule revealed that it had an apparent molecular mass of 400 kDa. SDS/PAGE of hybrid molecules, after treatment with heparitinase and chondroitinase ABC, revealed a core protein of 80 kDa. Using 1.8% polyacrylamide/0.6% agarose-gel electrophoresis, we deduced that the HS and CS were independently attached to one core protein. Because glomerular-basement-membrane HSPG is thought to be derived from mesangial cells and glomerular visceral epithelial cells and this molecule is involved in several kidney diseases, we investigated its synthesis in more detail. Anti-(rat glomerular-basement-membrane HSPG) monoclonal antibodies (JM403) and anti-(human glomerular-basement-membrane HSPG) polyclonal antibodies (both antibodies known to react with the large basement-membrane HSPG, perlecan) reacted strongly with HSPG obtained from both mesangial cells and glomerular visceral epithelial cells. However, the hybrid molecule did not react with these antibodies, suggesting that the HS side chain and the core protein were different from glomerular-basement-membrane HSPG. To quantify HS we performed an inhibition ELISA using mouse antibodies specific for glomerular-basement-membrane HS glycosaminoglycan side chains. Glomerular visceral epithelial cells produced significantly higher levels of HS (between 197.56 and 269.40 micrograms/72 h per 10(6) cells) than mesangial cells (between 29.8 and 45.5 micrograms/72 h per 10(6) cells) (three different cell lines; n = 3; P < 0.001). HS production by these cells was inhibited by cycloheximide, revealing that it was synthesized de novo. Expression of perlecan mRNA, demonstrated using reverse transcriptase PCR, was different in the two cell types. We conclude that glomerular visceral epithelial cells and mesangial cells have characteristic patterns of proteoglycan production. Glomerular visceral epithelial cells produced a hybrid proteoglycan containing CS and HS independently attached to its core protein.(ABSTRACT TRUNCATED AT 250 WORDS)